Does positron emission tomography/computed tomography change management in colorectal cancer?. Issue 4 (27th October 2016) - Falconer, Rachel; Connor, Saxon; Balasingam, Adrian; Eglinton, Tim
Abstract : Background: Positron emission tomography/computed tomography (PET/CT) is used pre‐operatively in patients with metastatic or recurrent colorectal cancer to identify those who have potentially curative disease. However, a recent randomized trial questioned the added benefit of PET/CT over conventional imaging in patients with liver metastases. The aim of this study was to determine the proportion of patients with colorectal cancer in whom PET/CT altered surgical management, in a single tertiary centre. Methods: This was a retrospective study of all patients with colorectal cancer who had a PET/CT for colorectal cancer, funded by the Canterbury District Health Board between 2010 and 2014. Results: Some 111 PET/CT scans were performed on 105 patients. A total of 38% of PET/CT were for patients with known or suspected liver metastases, 23% for suspected local recurrence and 18% for known or suspected lung metastases. Five scans were for post‐operative patients with a rising carcinoembryonic antigen and no attributable source on conventional imaging. PET/CT identified additional extrahepatic sites of disease in 19 of 111 (17%) scans in patients deemed to have potentially operable disease. Overall, PET/CT altered surgical management following six of 42 (14%) scans for patients with liver metastases, four of 20 (20%) scans for patients with lung metastases and six of 26 (23%) scans for patients with local recurrence. Conclusion: PET/CT remains a useful adjunct to conventional imaging in the pre‐operative workup of patients with colorectal cancer.